(untitled) (Journal of Institute of Science and Technology, 2025)
Eliminating pollutants using activated carbon is one of the economic and efficient solutions to address the water scarcity problem. Biomass-derived nanoporous activated carbons (ACs) were prepared from Buddleja wood powder with phosphoric acid activation and characterized by methylene blue and iodine adsorption, Boehm titration, and point of zero charge. Further AC were characterized using advanced instrumental analysis, such as Scanning Electron Microscopy (SEM), Raman scattering, and Fourier Transform Infrared Spectroscopy (FTIR). The maximum adsorption of iodine (667.0 mg/g) and methylene blue (140.84 mg/g) was observed at the ratio of 1:2 (precursor: phosphoric acid, BWC_2.0). The optimum conditions for adsorbing methylene blue were pH 10, 120 min contact time, adsorbent dose 1.6 g/L, and 100 mg/L methylene blue concentration. The BWC_2.0 turned the black color of the river water to colorless and reduced most of the contaminants to less than 20 %. Most of the pollutants, such as turbidity, oxidation-reduction potential (ORP), acidity, alkalinity, hardness, sulphate, phosphate, nitrate, iron, and chromium, are removed by more than 70% and chloride by 61%. The results implied that the Buddleja wood-derived activated carbon is useful in reducing pollutants from extremely polluted river water. In addition to adsorption of methylene blue from synthetic water, it works efficiently in the removal of pollutants from natural river water.